A functional genetic variation of SLC6A2 repressor hsa-miR-579-3p upregulates sympathetic noradrenergic processes of fear and anxiety. Issue 1 (December 2018) - Hommers, L.; Richter, J.; Yang, Y.; Raab, A.; Baumann, C.; Lang, K.; Schiele, M.; Weber, H.; Wittmann, A.; Wolf, C.; Alpers, G.; Arolt, V.; et al.
Abstract Increased sympathetic noradrenergic signaling is crucially involved in fear and anxiety as defensive states. MicroRNAs regulate dynamic gene expression during synaptic plasticity and genetic variation of microRNAs modulating noradrenaline transporter gene (SLC6A2 ) expression may thus lead to altered central and peripheral processing of fear and anxiety. In silico prediction of microRNA regulation ofSLC6A2 was confirmed by luciferase reporter assays and identified hsa-miR-579-3p as a regulating microRNA. The minor (T)-allele of rs2910931 (MAFcases = 0.431, MAFcontrols = 0.368) upstream ofMIR579 was associated with panic disorder in patients (p allelic = 0.004, n cases = 506, n controls = 506) and with higher trait anxiety in healthy individuals (p ASI = 0.029, p ACQ = 0.047, n = 3112). Compared to the major (A)-allele, increased promoter activity was observed in luciferase reporter assays in vitro suggesting more effectiveMIR579 expression andSLC6A2 repression in vivo (p = 0.041). Healthy individuals carrying at least one (T)-allele showed a brain activation pattern suggesting increased defensive responding and sympathetic noradrenergic activation in midbrain and limbic areas during the extinction of conditioned fear. Panic disorder patients carrying two (T)-alleles showed elevated heart rates in an anxiety-provoking behavioral avoidance test (F (2, 270) = 5.47, p = 0.005). Fine-tuning of noradrenaline homeostasis by aMIR579 genetic variation modulated central and peripheral sympathetic noradrenergic activation during fear processing and anxiety. This study opens new perspectives on the role of microRNAs in the etiopathogenesis of anxiety disorders, particularly their cardiovascular symptoms and comorbidities.